Analysis of the Structural Behavior Evolution of Reinforced Soil Retaining Walls Under the Combined Effects of Rainfall and Earthquake - Li, Xinxin; Cai, Xiaoguang; Li, Sihan; Huang, Xin; Zhu, Chen; Xu, Honglu (Buildings (Basel), 2025)
Major earthquakes and rainfall may occur at the same time, necessitating further investigation into the dynamic characteristics and responses of reinforced soil retaining walls subjected to the combined forces of rainfall and seismic activity. Three sets of shaking table tests on model retaining walls were designed, a modular reinforced earth retaining wall was utilized as the subject of this study, and a custom-made device was made to simulate rainfall conditions of varying intensities. These tests monitored the rainwater infiltration pattern, macroscopic phenomena, panel displacement, tension behavior, dynamic characteristics, and acceleration response of the modular reinforced earth retaining wall during vibration under different rainfall intensities. The results indicated the following. (1) Rainwater infiltration can be categorized into three stages: rapid rise, rapid decline, and slow decline to stability. The duration for infiltration to reach stability increases with greater rainfall. (2) An increase in rainfall intensity enhances the seismic stability of the retaining wall panel, as higher rainfall intensity results in reduced sand leakage from the panel, thereby diminishing panel deformation during vibration. (3) Increased rainfall intensity decreases the shear strength of the soil, leading to a greater load on the reinforcement. (4) The natural vibration frequencies of the three groups of retaining walls decreased by 0.21%, 0.54%, and 2.326%, respectively, indicating some internal damage within the retaining walls, although the degree of damage was not severe. Additionally, the peak displacement of the panel increased by 0.91 mm, 0.63 mm, and 0.61 mm, respectively. (5) The amplification effect of rainfall on internal soil acceleration is diminished, with this weakening effect becoming more pronounced as rainfall intensity increases. These research findings can provide a valuable reference for multi-disaster risk assessments of modular reinforced soil retaining walls.